Conduction through demyelinated plaques in multiple sclerosis: computer simulations of facilitation by short internodes. Issue 5 (May 1978) - Waxman, S G; Brill, M H
Abstract : Clinical and laboratory observations both suggest that it may be possible for action potentials to traverse, in a continuous manner and without interruption, demyelinated zones along some axons. This continuous mode of conduction requires the presence of sufficient numbers of sodium channels in the demyelinated region. One of the factors which will tend to prevent such conduction is the impedance mismatch at sites of focal demyelination, which may result in a reduction in current density sufficient to cause conduction failure. As part of an effort to examine the conditions which would promote conduction into, and beyond, the demyelinated region, we examined, using computer simulations, the effects of reduction in length of the proximal internodes closest to the demyelinated region. Our results indicate that reduction in length of the two internodes closest to the demyelinated region. to approximately one-third of normal length or less, will facilitate conduction beyond the plaque. The results suggest that reductions in internode length, which have been histologically observed along some demyelinated fibres, may have functional significance in terms of facilitating conduction past focally demyelinated zones.